Формування особистості майбутніх інженерів-педагогів у процесі самостійної роботи з педагогічних дисциплін - Фіногєєва, Т. Є. (НТУ "ХПІ", 2014)
Виконано аналiз поняття "іженер-педагог" в педагогiчних i психологiчних дослідженнях. Охарактеризовано типовi завдання майбутнх iнженерiв-педагогiв. Описано особливостi формування особистостi майбутніх iнженерiв-педагогiв у процесі самостійної роботи з педагогiчних дисциплін. Розглянуто питання розвитку самостiйностi як професійно важливої якостi особистостi студентiв іженерно-педагогiчних спеціальностей у процесі самоосвіти, самооцінювання i самоконтролю. Запропоновано види самостійної роботи студентiв iнженерно-педагогiчних спеціальностей при виконаннi пізнавальних завдань з дисципліни "Дидактичні основи професійної освіти".

It is proved that in higher vocational school a gap between the needs of the global society and education outcomes between the objective requirements of time and the general lack of educational level, between professional orientation and identity needs to meet a variety of cognitive harmony of interests between modern methodological approaches developed and sciences archaic forms of learning. We believe that one way to overcome these problems is to improve the organization of the learning process in higher education through the introduction of new forms and methods of self-study in order to develop students' capacity for self-education, commitment to continuous professional improvement. It is proved that engineering pedagogical education is a synthesis and equivalence of two main components: humanities and social and vocational. The analysis of the concept of „teacher-engineer" in educational and psychological research. It was found that the teacher-engineer - a specialist with higher integrated pedagogical and technical education, which manages educational and productive activities
Formation of the person of the future teacher-engineers in the independent work in pedagogical subjects
Keywords: професійне самовдосконалення; самостійна робота; педагогiчнi дисципліни; самооцінка; teacher-engineer; professional self-improvement; professional orientation; professional competence; independent work; pedagogical discipline